TANTANGAN NASIONAL DAN GLOBAL UNTUK MENINGKATKAN MUTU SEKOLAH/MADRASAH - Ifrila Hidayatus Soffah; Samsul Susilawati (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This research aims to identify national and global challenges in improving the quality of schools/madrasahs, along with appropriate strategies to address and minimize their negative impacts. This is a qualitative study utilizing a literature review approach. Data sources were gathered from previous research, news articles, and other documents relevant to the discussed theme. The collected data were analyzed using content analysis techniques. The results of this study indicate several national challenges in improving school/madrasah quality: a lack of educational equity, varying teacher quality combined with distribution issues, and a continuously changing, overly complex curriculum. Strategies to address these national challenges include achieving educational equity, managing teacher distribution while providing training for educators and staff, and conducting training for curriculum implementation. Meanwhile, global challenges in improving school/madrasah quality include the digitalization of education, the rise of artificial intelligence, and the low competitiveness of graduates in the international arena. Strategies to address these global challenges involve creating vision and mission statements that integrate with technology, ensuring equal distribution of educational digital facilities, providing training on the use of artificial intelligence for educators and staff, and establishing specialized programs to boost the competitiveness of graduates in the international workforce.